Primary dysmenorrhea: pathophysiology, improvement of diagnostic and treatment possibilities - T.V. Fartushok; N.V. Fartushok (Medičnì Perspektivi)
Primary dysmenorrhea is one of the types of gynecological pathology, the frequency of which is 45-53% in girls and young women aged 13 to 45 years, which is not given enough attention in diagnosis and treatment.The pathogenesis takes into account the increased secretion of prostaglandins F2α and E2 in the period from the beginning of pregnancy to birth, which cause pelvic pain.The diagnosis is based on the patient's history, symptoms, examination, the treatment is aimed at improving the quality of life by prescribing nonsteroidal anti-inflammatory drugs, hormonal contraceptives and the use of non-medicinal means. Purpose: to specify some links in the pathogenesis of primary dysmenorrhea and, taking into account its multicomponent nature, to evaluate the effectiveness of the proposed treatment. Under observation there were 68 women who were divided into 2 groups: 34 women with primary dysmenorrhea (main group) and 34 healthy women (control group).The diagnosis of primary dysmenorrhea was established on the basis of complaints of patients about painful menstruation and accompanying symptoms during consultations with a gynecologist and endocrinologist.Treatment of patients in the main group was carried out with the drug, which includes Vitex agnus castus L, indinol-3-carbinol, 3,3-diindolyl-methane, extract of passionflower, California Eschscholzia. In women with typical symptoms, dysmenorrhea can be diagnosed on the basis of medical information without physical pelvic examination, empirical treatment should be initiated, including nonsteroidal anti-inflammatory drugs and/or oral contraceptives, because it is a functional condition resulting from an imbalance in the hormonal regulation of myometrial contraction. As a result of the proposed treatment, pain disappeared completely in 70% of patients (23/34), as well as vegetative-vascular (from 18 to 2% of patients), vegetative (from 10 to 1% of patients), metabolic and endocrine disorders (from 15 to 2% female patients), disorders of the emotional and mental sphere (from 25 to 10% of patients). Improvement in quality of life was noted by 80% (26/34) of patients, improvement in working capacity – by 70% (23/34) of patients, after 2 months – by 95% (31/34) and 85% (28/34), respectively, after 3 months all examined patients with primary dysmenorrhea noted an improvement in the quality of life and an increase in work capacity. Sexually active women with symptoms of inflammatory processes of the genital tract, severe dysmenorrhea should undergo pelvic examination. In view of safety and high therapeutic efficiency, the drug based on Vitex agnus castus can be offered for the treatment over the period lasting at least for3 months for girls and young women aged 13 to 45 years with primary dysmenorrhea.